Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe SnowballThrowingMelalui Media Pembelajaran Audio-Visual Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VIII SMP 3 Bangkinang Materi Aljabar - Ihsan, Muhammad; Astuti; Wahyuni, Molly (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This research was motivated by the low critical thinking skills of class VIII students at SMP Negeri 3 Bangkinang. One solution to overcome this problem is to apply snowball throwing learning. This research aims to determine whether snowball throwing learning through audio-visual learning media influences students' critical thinking abilities or not. This research is a quasi-experimental study using a randomized control group pretest-posttest design. The research subjects consisted of class VIIIA, totaling 32 students, and VIIIC, totaling 30 students. The sampling technique used was simple random sampling. The research instruments used were observation sheets and test questions on students' critical thinking abilities. The results of the research show that the Snowball Throwing model through Audio-Visual learning media has an effect on students' mathematical critical thinking abilities. With the increase in the average student score after the learning model was implemented in the experimental class from the average score before the learning model was implemented, H also became a reference that the application of the Snowball Throwing type cooperative learning model through audio-visual learning media can influence and improve thinking abilities. critical of class VIII students at SMPN 3 Bangkinang.